A Pilot Study of an Interprofessional Program Involving Dental, Medical, Nursing, and Pharmacy Students - Tabrizi, Maryam; Lee, Wei-Chen (Frontiers in Public Health, 2020)
Objective: The silent epidemic of oral diseases disproportionately affects disadvantaged communities, especially the elderly who have complex needs for healthcare. This study was to evaluate a pilot oral health interprofessional program that provided hands-on experiences for students across four disciplines: dentistry, medicine, nursing, and pharmacy. Methods: The 8-week program was built on four pedagogical principles: care, critical thinking, communication, and collaboration coupled with the 4Ms model: what matters, medication, mentation, and mobility. The curriculum contained four scenarios of a dental complication in an elderly: Alzheimer’s Disease, oral cancer, Parkinson’s Disease, and stroke. A mixed-methods approach was used to evaluate this pilot program. Results: The average score of knowledge and attitude has increased from 2.94 to 4.39 (p-value less than 0.05) on a 5-point Likert scale. The qualitative responses also showed that students became more confident in practicing within the Age-Friendly health system. Discussion: By the end of the program, all students recognized the significance of the interprofessional program to improve their knowledge and skills to work with professionals across disciplines. Two key features that contributed to the success of the program were (1) an interprofessional education that increased students’ awareness of other types of services and (2) four scenarios that allowed students to solve the case and gain hands-on experience. Conclusion: An interprofessional education may equip students with competence to address the health of geriatric patients. Materials used in this study could be shared and adapted to prepare learned for other scenarios that require interprofessional team practice.